Kanon historiograficzny w literaturoznawstwie polsko-ukraińskim XVIII–XX wieku - Henc, Adriana (Studia Ukrainica Posnaniensia, 2022)
The article investigates the theoretical and practical principles of creating a canon in Polish and Ukrainian historical and literary syntheses in the context of European historiographical traditions. The core criteria of selection of historical and literary material are singled out, and taxonomic tendencies in the histories of literature from the 18th–20th centuries are considered. The main aspects of the canonization of texts in Ukrainian and Polish historiographical corpora are clarified, which are primarily reflected in the formal characteristics, criteria for selecting literary texts, the author’s interpretations, conceptual approaches and the methodological basis. The article articulates the main achievements of literary historians of the 18th–20th centuries, as well as comprehensively defining the methodology for creating a holistic and scientifically sound corpus of the history of Ukrainian and Polish literature.